2020
DOI: 10.1016/j.jsxm.2020.07.079
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Prospective Study of Grafting with Collagen Fleece TachoSil in Patients with Peyronie's Disease

Abstract: Background A xenograft consisting of equine collagen coated with human fibrinogen and thrombin (TachoSil; Baxter, CA) has recently been introduced in grafting procedures for Peyronie’s disease (PD). Aim To describe the results of a multicenter prospective registry on patients with PD undergoing plaque incision or and grafting (PIG) or plaque excision and grafting (PEG) with collagen fleece TachoSil, to evaluate the efficacy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Multiple literature reviews reported that these grafts are comparable regarding clinical outcomes; however, the heterogeneity of the series published makes it difficult to conclude ( 1 - 3 , 41 - 43 ). Nevertheless, TachoSil stands out as an operative time saver compared to others ( 3 , 36 , 37 , 44 , 45 ). Due to its ready availability, sutureless application, and hemostatic effect, TachoSil gained popularity in PD surgery.…”
Section: Discussionmentioning
confidence: 86%
“…Multiple literature reviews reported that these grafts are comparable regarding clinical outcomes; however, the heterogeneity of the series published makes it difficult to conclude ( 1 - 3 , 41 - 43 ). Nevertheless, TachoSil stands out as an operative time saver compared to others ( 3 , 36 , 37 , 44 , 45 ). Due to its ready availability, sutureless application, and hemostatic effect, TachoSil gained popularity in PD surgery.…”
Section: Discussionmentioning
confidence: 86%
“…[17][18][19][20] Non-steroidal anti-inflammatory drugs (NSAIDs), penile traction therapy (PTT), collagenases, and shortening or lengthening surgical procedures are some treatment options for PD. [21][22][23][24] In recent years, ESWT has proven to be an effective treatment in selected patients with ED and PD, to improve erectile function and relieve penile pain, respectively. [4][5][6] ESWT is generally described as a safe andrological procedure characterized by mild and transient side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Oral PDE5Is, intracavernous or topical alprostadil, vacuum devices, and penile prostheses are some therapeutic options for ED 17–20 . Non‐steroidal anti‐inflammatory drugs (NSAIDs), penile traction therapy (PTT), collagenases, and shortening or lengthening surgical procedures are some treatment options for PD 21–24 . In recent years, ESWT has proven to be an effective treatment in selected patients with ED and PD, to improve erectile function and relieve penile pain, respectively 4–6 …”
Section: Discussionmentioning
confidence: 99%
“…16 Moreover, TachoSil displays additional hemostatic effects that minimize the risk of hematoma and, subsequently, protect against infections or other perioperative complications. 17 Of note, the collagen fleece has a minimal risk of contraction and, thus, leads to preservation or even increase in penile length compared to the preoperative status. 18 Another important advantage of TachoSil is its low cost.…”
Section: Discussionmentioning
confidence: 99%